Effects of Music Listening upon online CS Students - Borovina Josko, João Marcelo; Zampirolli, Francisco de Assis (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2022: Anais do XXXIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2022.224795, 2022)
One of the challenges Computer Science (CS) tutors confront is applying methods to sustain their students' enthusiasm for learning topics perceived as complex, especially in online courses. The use of music has revealed several contributions in the educational context but is underutilized in the CS background. Hence, we conducted an exploratory case study on seven online groups of four different CS subjects to capture (using a survey) students' perspectives (N=97, 25% women, Age average=23) on their experience listening to music before and after each lecture and demonstration. Our quantitative and qualitative analyses strongly indicated that music listening positively affected students' mood, energy, calmness, and attitude toward CS topics.